Advanced clinical practitioners' experience of establishing a workplace jurisdiction. (3rd July 2022) - Lawler, Jessica; Maxwell, Elaine; Radford, Mark; Leary, Alison
ABSTRACT: Background: In 2017 a national policy framework for advanced clinical practice in England was introduced by Health Education England, to establish clarity around the level of practice. Whether the implementation of this framework has resulted in adoption of advanced clinical practice into public and workplace jurisdictions is yet to be explored. Aims: This health service workforce evaluation aims to explore the views and opinions of Advanced Clinical Practitioners and trainees in England on their experiences since the implementation of the 2017 framework. Methods: This is secondary analysis of a workforce dataset. A self-completed questionnaire was distributed via the Association of Advanced Practice Educators United Kingdom aimed at those undertaking Advanced Clinical Practitioner education or who are practicing at this level. Semi-structured phone interviews were carried out with a subset of this group on their views and opinions to obtain depth of insight. Questionnaires were summarized using descriptive statistics in Excel and interviews analysed using thematic analysis. Results: The identity of the advanced clinical practitioner role is developing. Of questionnaire respondents, 29% thought their line manager didn't understand their role, and 42% thought that patients didn't understand their role. Three quarters (75%) had access to clinical supervision. Interview respondents reported restriction in their role as a result of a perceived lack of understanding and awareness from colleagues. Interviewees reported that they had to spend time explaining their role to colleagues, patients and managers. Conclusions: Advanced Clinical Practitioners in this evaluation perceived a lack of clarity and understanding around their role from their colleagues, patients and managers. Relevance to clinical practice: This suggests that Advance Clinical Practitioners are currently under-prepared to negotiate jurisdictions, a key aspect in the introduction of a new role.